Sex diversity in proximal tubule and endothelial gene expression in mice with ischemic acute kidney injury. Issue 14 (23rd July 2020) - Viñas, Jose L.; Porter, Christopher J.; Douvris, Adrianna; Spence, Matthew; Gutsol, Alex; Zimpelmann, Joseph A.; Tailor, Karishma; Campbell, Pearl A.; Burns, Kevin D.
Abstract: Female sex protects against development of acute kidney injury (AKI). While sex hormones may be involved in protection, the role of differential gene expression is unknown. We conducted gene profiling in male and female mice with or without kidney ischemia–reperfusion injury (IRI). Mice underwent bilateral renal pedicle clamping (30 min), and tissues were collected 24 h after reperfusion. RNA-sequencing (RNA-Seq) was performed on proximal tubules (PTs) and kidney endothelial cells. Female mice were resistant to ischemic injury compared with males, determined by plasma creatinine and neutrophil gelatinase-associated lipocalin (NGAL), histologic scores, neutrophil infiltration, and extent of apoptosis. Sham mice had sex-specific gene disparities in PT and endothelium, and male mice showed profound gene dysregulation with ischemia–reperfusion compared with females. After ischemia PTs from females exhibited smaller increases compared with males in injury-associated genes lipocalin-2 ( Lcn2 ), hepatitis A virus cellular receptor 1 ( Havcr1 ), and keratin 18 ( Krt18 ), and no up-regulation of SRY-Box transcription factor 9 ( Sox9 ) or keratin 20 ( Krt20 ). Endothelial up-regulation of adhesion molecules and cytokines/chemokines occurred in males, but not females. Up-regulated genes in male ischemic PTs were linked to tumor necrosis factor (TNF) and Toll-like receptor (TLR) pathways, while female ischemic PTs showed up-regulated genes in pathways related to transport. The data highlight sex-specific gene expression differences in male and female PTs and endothelium before and after ischemic injury that may underlie disparities in susceptibility to AKI.